Martial arts in the system of physical education of students of younger adolescence - Chub S.A. ,; Agafonov S.V. ,; Zhikharev D.A. ,; Lobanova E.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and experimentally test the effectiveness of a set of exercises to improve the motor qualities of younger adolescents aged 10-11 years using hand-to-hand combat. Methods and structure of the study. The study was conducted on the basis of secondary school No. 78 in the city of Rostov-on-Don, which was attended by 5th grade students aged 10-11 years. Methods of scientific research: pedagogical testing, pedagogical experiment, methods of mathematical statistics. The study included three consecutive stages. The experiment involved 30 boys of the fifth grade, who were divided into control and experimental groups of 15 people each. Results and conclusions. The results obtained during the experiment clearly demonstrated the effectiveness of the developed complex used in physical education lessons and general physical training classes for students aged 10-11. The authors recommend using this complex when solving the problem of developing physical qualities in students when organizing physical education in a general education institution.